Duration of frontline therapy and impact on clinical outcomes in newly diagnosed multiple myeloma patients not receiving frontline stem cell transplant. (24th September 2022) - Ailawadhi, Sikander; Ogbonnaya, Augustina; Murty, Sharanya; Cherepanov, Dasha; Schroader, Bridgette Kanz; Romanus, Dorothy; Farrelly, Eileen; Chari, Ajai
Abstract: Background: Extended first‐line therapy (1LT) has improved clinical outcomes in newly diagnosed multiple myeloma (NDMM). This retrospective study of NDMM patients evaluated the relationship between dose‐attenuation of 1LT and duration of therapy (DOT) and DOT on outcomes. Methods: Adults with NDMM not undergoing stem cell transplant (SCT) from January 1, 2012 toMarch 31, 2018 from the Integrated Oncology Network were included; 300 were randomly selected for chart review. 1LT DOT, time to next treatment (TTNT), progression‐free survival (PFS), and overall survival (OS) were estimated using Kaplan–Meier analysis. Marginal structural models evaluated relationships between DOT and TTNT, PFS, and OS at 2 years accounting for confounders and survival bias from the time‐dependent nature of DOT. Results: Of 300 chart‐reviewed patients, 93 were excluded for incomplete data or meeting exclusion criteria. Among 207 NDMM patients, median age was 74 years; 146 (70.5%) did not receive dose‐attenuation during 1LT. Patients with short DOT were older, frailer, with a higher comorbidity burden, and a significantly lower proportion had an Eastern Cooperative Oncology Group PS = 0. As DOT increased, more patients underwent dose‐attenuation ( p  < 0.0001). The median 1LT DOT was 20.9 (95% confidence interval [CI]: 13.9, 26.4) versus 4.2 months (95% CI: 3.2, 4.9) for patients receiving versus not receiving dose‐attenuation, respectively ( p  < 0.0001). After accounting for survival bias, confounder‐adjusted TTNT was prolonged with each additional month of 1LT (odds ratio [OR]: 0.76 [95% CI: 0.75, 0.78]); likelihoods of risks of disease progression (OR: 0.87 [95% CI: 0.86, 0.88]) and death at 2 years (OR: 0.72 [95% CI: 0.70, 0.74]) were reduced with each month of 1LT ( p  < 0.0001 for all outcomes). Conclusions: Dose‐attenuated 1LT was associated with longer DOT among patients with non‐SCT NDMM. Each additional month of 1LT was associated with a reduced adjusted likelihood of disease progression and death at 2 years. Dose‐attenuation of 1LT can extend DOT; longer DOT may improve clinical outcomes. Abstract : Frequently, transplant‐ineligible patients are those who are frail and/or elderly, highlighting an unmet medical need for tolerable therapies; one approach to sustaining response balanced with tolerability is the use of maintenance or dose‐attenuated therapies. Among newly diagnosed multiple myeloma patients who did not receive stem cell transplant, dose‐attenuated first‐line therapy was associated with longer duration of therapy vs first‐line therapy without dose‐attenuation. Each additional month of first‐line therapy was associated with a reduced adjusted likelihood of disease progression and death at 2 years.